2020
DOI: 10.1186/s13569-020-0127-0
|View full text |Cite
|
Sign up to set email alerts
|

The immune microenvironment of uterine adenosarcomas

Abstract: Background: Uterine adenosarcoma (UA) is an extremely rare sarcoma subtype. There has been limited evaluation of the immune microenvironment in these tumors. The objective of this study is to examine and describe the immune infiltrate and PD-1/PD-L1 expression in UA and to correlate these changes in the tumor micro-environment with the overall survival status or the disease-free survival status (DFSS), respectively.Methods: Patients (pts) treated at our center from 1982 to 2014 with UA were identified. Fifteen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 30 publications
0
7
1
Order By: Relevance
“…26,32,33 An association between high numbers of CD8 + T-lymphocytes, better overall survival, and prolonged recurrence-free survival was indicated in a study conducted by de Jong et al 33 Furthermore, Ali et al showed no correlation between tumor-associated macrophage density and overall survival status in uterine adenosarcoma cases. 20 In contrast, we found the infiltration of higher tumorassociated macrophage counts to be correlated with an unfavorable overall survival and disease-free survival rate. Additionally, Ali et al found that higher CD8 + T-cell density was associated with a better overall survival rate.…”
Section: Discussioncontrasting
confidence: 61%
See 2 more Smart Citations
“…26,32,33 An association between high numbers of CD8 + T-lymphocytes, better overall survival, and prolonged recurrence-free survival was indicated in a study conducted by de Jong et al 33 Furthermore, Ali et al showed no correlation between tumor-associated macrophage density and overall survival status in uterine adenosarcoma cases. 20 In contrast, we found the infiltration of higher tumorassociated macrophage counts to be correlated with an unfavorable overall survival and disease-free survival rate. Additionally, Ali et al found that higher CD8 + T-cell density was associated with a better overall survival rate.…”
Section: Discussioncontrasting
confidence: 61%
“…[12][13][14][15][16] A meta-analysis reported by Lu et al showed that elevated PD-L1 expression was correlated with poor differentiation and advanced stages in endometrial cancer, whereas the prognostic effect of PD-L1 on survival was not significant. 15 The expression of PD-L1, along with immune cell infiltration in adenosarcomas, was first reported by Ali et al 20 The authors demonstrated rare (1%) PD-L1 staining in 3 of 15 cases, and found that PD-L1 expression did not affect disease-free survival or overall survival rates. 20 In our series, three of 20 tumors had TPS PD-L1 positivity with a 1% cut-off value and all were high-grade in nature.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Its activity in our patient suggests that it would be worthy of a prospective investigation in mullerian adenosarcoma. In fact, PD-L1 expression, a predictive factor of response to immune checkpoint inhibition, although absent in our case, has been reported in a subset of uterine adenosarcomas [ 10 ].…”
Section: Discussionmentioning
confidence: 54%
“…Previous studies have found that limited T lymphocyte infiltration or low immunogenicity of the TME is the main reason for the failure of treatment ( 98 , 99 ). The interaction between tumor cells and immune cells is a core feature of the TME ( 100 , 101 ). Owing to the high plasticity of immune cells, tumor cells promote the maturation, differentiation and recruitment of immunosuppressive cells by secreting IL-10, TGF-β, and VEGF to construct an immunosuppressive TME ( 102 , 103 ).…”
Section: Ros and Tmementioning
confidence: 99%